2009
DOI: 10.1021/jo9005975
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,5-Dihydrofuran-Fused Quinones from Ether-Tethered Diiododiyne

Abstract: Biologically interesting 2,5-dihydrofuran-fused quinones were synthesized via the ruthenium-catalyzed [2 + 2 + 2] cycloaddition of an ether-tethered diiododiyne with alkynes, copper-catalyzed Ullmann coupling of the resultant fused p-diiodobenzenes with methanol or allyl alcohol, and subsequent oxidation of phenol derivatives. The double Claisen rearrangement of the bis(allyl) ether product furnished a diallylhydroquinone derivative, which underwent iron-catalyzed oxidation, ring-closing metathesis, and dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 39 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…2,5-Dihydrofurans are important heterocycles that are widely used in pharmaceuticals and as flavor and fragrance compounds and are found in naturally occurring and biologically important molecules . Accordingly, substantial attention has been given to developing efficient methods for the synthesis of 2,5-dihydrofurans.…”
Section: Introductionmentioning
confidence: 99%
“…2,5-Dihydrofurans are important heterocycles that are widely used in pharmaceuticals and as flavor and fragrance compounds and are found in naturally occurring and biologically important molecules . Accordingly, substantial attention has been given to developing efficient methods for the synthesis of 2,5-dihydrofurans.…”
Section: Introductionmentioning
confidence: 99%
“…216 This capability enabled synthesis of 2,5-dihydrofuran-fused quinones from ether-tethered diiododiynes and acetylene (not shown). 217 Interestingly, in a 2010 kinetic study, Yamamoto investigated the performance of a series of polymethylcyclopentadienyl ruthenium complexes in [2+2+2] cycloadditions 218 cycloadditions of diiodotriynes was reported by Aubert and Gandon in 2011 (not shown). 219 Intramolecular Cp*RuCl(cod)-catalyzed alkyne [2+2+2] cycloadditions of acyclic triynes have been utilized to great effect in the total synthesis of natural products.…”
Section: [2+2+2]mentioning
confidence: 91%
“… In 2006, the same authors applied these conditions to intramolecular [2+2+2] cycloadditions of acyclic diiodotriynes to form hexasubstituted diiodinated benzene derivatives (Scheme ) and of diiodo-terminated 1,6-diynes and monoalkynes to form iodinated benzene derivatives bearing a wide range of functional groups (not shown) . This capability enabled synthesis of 2,5-dihydrofuran-fused quinones from ether-tethered diiododiynes and acetylene (not shown) . Interestingly, in a 2010 kinetic study, Yamamoto investigated the performance of a series of polymethylcyclopentadienyl ruthenium complexes in [2+2+2] cycloadditions and found that for reactions of diiododiyne and acetylene, 1,2,4-Me 3 CpRuCl­(cod) and MeCpRuCl­(cod) were the most efficient catalysts.…”
Section: Six-membered Ring Formationmentioning
confidence: 99%
“…19 Treatment with KOt-Bu, 1,10-phenanthroline, and CuI under microwave irradiation (300 W, 150 °C) mainly provided the undesired monosubstituted product ( Table 2, entry 2). 20 However, under the same conditions, the diiodo aryl compound 4b was converted into the desired product 4b in a 77% yield ( In conclusion, we have achieved the synthesis of the angucycline aglycon core involving a quinone in the B ring and a nonaromatic hydroxylated C ring via the Masamune-Bergman cyclization from a 1,2-dialkynylbenzene derivative precursor. This synthetic method suggests a new synthetic route for the construction of natural products containing naphthoquinone skeletons.…”
mentioning
confidence: 88%
“…19 Treatment with KOt-Bu, 1,10-phenanthroline, and CuI under microwave irradiation (300 W, 150 °C) mainly provided the undesired monosubstituted product (Table 2, entry 2). 20 However, under the same conditions, the diio-do aryl compound 4b was converted into the desired product 4b in a 77% yield (Table 2, entry 3). Interestingly, no aromatized byproduct was caused by β-elimination.…”
mentioning
confidence: 99%